Prevalence of gestational diabetes and subsequent Type 2 diabetes among U.S. women. (July 2018) - Casagrande, Sarah Stark; Linder, Barbara; Cowie, Catherine C.
Highlights: The national prevalence of GDM among U.S. women was 7.6%. Among women with GDM, 19.7% had a subsequent diagnosis of diabetes. Women with GDM, familial diabetes, and obesity should be monitored for dysglycemia. Abstract: Aims: The true prevalence of gestational diabetes (GDM) in the United States is unknown. This study determined the prevalence of GDM and a subsequent diagnosis of diabetes in a nationally representative sample of U.S. women. Methods: The crude and age-adjusted prevalence of GDM and subsequent diabetes were evaluated by sociodemographic and health-related characteristics among women age ≥20 years in the National Health and Nutrition Examination Surveys, 2007–2014 (N = 8185). Logistic regression analyzed independent factors associated with GDM and subsequent diabetes. Results: The prevalence of GDM was 7.6%. Women who were Mexican American (vs. non-Hispanic white), had ≥4 live births (vs. 1), had a family history of diabetes, or were obese (vs. normal weight) had a higher age-standardized prevalence of GDM (each p < 0.04). Among women with a history of GDM, 19.7% had a subsequent diagnosis of diabetes; subsequent diabetes diagnosis was higher for those with health insurance, more time since GDM diagnosis, greater parity, family history of diabetes, and obesity, and lower for those with higher education and income (all p ≤ 0.005). By logistic regression, significant factors associated with GDM were age at first birth, parity, family history of diabetes, and obesity; significant factors for subsequent diabetes were older age, greater years since GDM diagnosis, less education, family history of diabetes, and obesity (each p < 0.01). Conclusions: The prevalence of GDM in the U.S. was 7.6%, with 19.7% of these women having a subsequent diabetes diagnosis. Women with a history of GDM, family history of diabetes, and obesity should be carefully monitored for dysglycemia.